2022
DOI: 10.3390/life12111803
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts and Future Applications of Non-Invasive Functional and Anatomical Evaluation of Coronary Artery Disease

Abstract: Over the last decades, significant advances have been achieved in the treatment of coronary artery disease (CAD). Proper non-invasive diagnosis and appropriate management based on functional information and the extension of ischemia or viability remain the cornerstone in the fight against adverse CAD events. Stress echocardiography and single photon emission computed tomography are often used for the evaluation of ischemia. Advancements in non-invasive imaging modalities such as computed tomography (CT) corona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 194 publications
0
14
0
Order By: Relevance
“…[16] The value of cardiac CT in assessing cardiac function and the coronary artery morphology has also been increasingly recognized, especially multiple-slice CT (MSCT). [19][20][21] Most researchers have been focusing on the accuracy and reproducibility of each imaging technique, but readily ignored the interchangeable value of 1 technique to another. [18] The objective of this study was to investigate the correlation and agreement between cardiac 3-Tesla MRI and 256-slice MSCT or 2-dimensional ECHO in evaluation of cardiac volume and function.…”
Section: Introductionmentioning
confidence: 99%
“…[16] The value of cardiac CT in assessing cardiac function and the coronary artery morphology has also been increasingly recognized, especially multiple-slice CT (MSCT). [19][20][21] Most researchers have been focusing on the accuracy and reproducibility of each imaging technique, but readily ignored the interchangeable value of 1 technique to another. [18] The objective of this study was to investigate the correlation and agreement between cardiac 3-Tesla MRI and 256-slice MSCT or 2-dimensional ECHO in evaluation of cardiac volume and function.…”
Section: Introductionmentioning
confidence: 99%
“…Lp(a) also upregulates expression of urokinase and urokinase receptors on monocytes and, therefore, activation of plasmin that promotes ECM shrinkage [ 111 ]. A different mechanism refers to OxPLs, as a part of apo(a), that facilitate apoptosis of endoplasmic-reticulum-stressed macrophages and, therefore, plaque necrosis [ 112 , 113 ]. Lp(a), thus, possesses a crucial role not only in the early phases of atherosclerosis but also later during the sequence of events that result in destabilization of atherosclerotic plaques ( Figure 3 ).…”
Section: Role Of Lp(a) On Atherosclerosismentioning
confidence: 99%
“…Furthermore, several studies have demonstrated an association between circulating Lp(a) and restenosis after percutaneous transluminal coronary angioplasty (PTCA). Lp(a) has been described as an independent predictor of restenosis, with higher levels correlated with higher risk of restenosis [ 113 , 201 , 202 , 203 ] or with an increased degree of restenosis [ 204 ]. Nevertheless, studies that reveal no significant correlation between Lp(a) and restenosis after PTCA have been developed so far [ 205 , 206 ].…”
Section: Lp(a) and Neointimal Hyperplasiamentioning
confidence: 99%
“…Performance of endoscopy, laryngoscopy, and biopsy is the invasive diagnostic procedures used traditionally 9,10 . At present, with the advancement of technology, apart from these invasive methods non‐invasive techniques such as computed tomography (CT) scan, positron emission tomography (PET), and magnetic resonance imaging (MRI) are followed as an early detection of HNSCC 11,12 …”
Section: Introductionmentioning
confidence: 99%
“…9,10 At present, with the advancement of technology, apart from these invasive methods non-invasive techniques such as computed tomography (CT) scan, positron emission tomography (PET), and magnetic resonance imaging (MRI) are followed as an early detection of HNSCC. 11,12 Surgery, chemotherapy, and radiation therapy are the presently used conventional methods in HNSCC treatment. However, these methods have serious adverse effects, impacting on the daily lifestyle/standards of living of patients.…”
mentioning
confidence: 99%